Project office : a key to managing projects effectively - Block, Thomas R. (Crisp pub. Menlo ParkUS, 1998)
Focuses on nurturing project managemnet capabilities by establishing and maintaining a project office. Defines project management and project office, and reviews 5 functions which a project office can carry out including: supplying project management support to the project team; and providing project management training. Also shows how project offices can be established to support these functions.